PUBLIC RELATIONS STRATEGY FOR IMPROVING QUALITY OF SERVICE TO PATIENTS (Qualitative Descriptive Study at Muslimat Ponorogo Hospital) - Putri, Aulia Amana (UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Abstrack: RSU Muslimat Ponorogo focuses on the quality of service to patients. This study aims to determine how the strategy is carried out by public relations. This article uses a descriptive type of research with a qualitative approach. Researchers get data from interviews, observation, and documentation. The results showed that the public relations strategy of the Muslimat Ponorogo Hospital in improving the quality of service to patients was in accordance with the theory presented by the researcher. First, the human relations strategy is to maintain good relations with employees and customers or patients. Second, the community relations strategy is to maintain good relations with the community and communities around the hospital. Third, the media relations strategy is to use mass media, be it print, electronic or new media (internet). Fourth, it was found that the inhibiting factors faced by public relations in improving service quality, such as registration queue problems, lack of parking area, and lack of human resources. Meanwhile, supporting factors were also found, namely the presence of introductory media used, including conventional media, namely radio and television, outdoor media, namely billboards, and new media (internet), namely the internet, social media websites, Facebook, Instagram, and YouTube.